Students’ Perception on the Use of Edmodo for Group Discussions: Insights from the English Education Program at Pattimura University - Ulath, Safitri; Lekatompessy, Jeny; Loppies, Hellien (Huele: Journal of Applied Linguistics, Literature and Culture, 2022)
This study investigates the effectiveness of Edmodo as a digital platform for group discussions in language learning, focusing on students' experiences in the English Education Program at Pattimura University. Through a mixed-method approach, data were collected from 34 undergraduate students via structured questionnaires examining student participation, lecturer involvement, and peer interaction, complemented by in-depth interviews with five selected participants. The quantitative findings revealed significant positive perceptions toward Edmodo's role in facilitating discussions, with 85% of students reporting increased participation comfort (M = 3.3, SD = 0.6) and 90% valuing lecturer feedback (M = 3.5, SD = 0.4). Additionally, 78% of students indicated enhanced peer interaction comfort (M = 3.2, SD = 0.6), though technical challenges affected response timing satisfaction (65%, M = 2.9, SD = 0.8). Qualitative analysis identified key themes including reduced anxiety in expression, the critical role of lecturer guidance in maintaining discussion quality, and the development of supportive learning communities despite technological constraints. While Edmodo successfully addresses traditional classroom participation barriers and fosters thoughtful engagement, the platform's effectiveness is influenced by factors such as internet connectivity, lecturer engagement patterns, and peer response timing. These findings contribute to understanding how digital platforms can effectively support language learning through group discussions, suggesting the need for balanced integration of technical infrastructure improvements and pedagogical strategies to optimize online learning experiences in higher education.